The application of discovery learning as an effort to improve mathematical problem solving skills - Qurohman, M. Taufik; Romadhon, Syaefani Arif (International Journal of Trends in Mathematics Education Research, 2023)
Research conducted is a type of experimental research that has the following objectives: (1) to know the correlation between the learning achievement of students who use the discovery learning method and the conventional method in the applied math course , (2) to know the level of effectiveness of student outcomes using conventional and discovery learning methods, (3) to know the level of effectiveness of student of learning results by using the discovery learning method and conventional methods. The research conducted has a population of D3 Mechanical Engineering study program students in Semester 2 Academic Year 2022/2023 Harapan Bersama PolytechnicSamples taken using grade 2A and 2C randomly where the two gradees with the division of grade 2A is the experiment grade and grade 2C is the control grade. The series of processes in the research method consists of preliminary tests, namely validity, reliability, difficulty level, and question differentiation. After being given the learning treatment, then analyzed by statistical tests. The results of the analysis provide an overview the results that in an experimental grade with an average result of 78 and a control grade with average results. Result of 62, then a statistical test is obtained  sedangkan  from the analysis results, it can be concluded that students who get treatment with the discovery learning method get better learning outcomes than the class that does not. do not get discovery learning treatment.